Sintesis dan Kararkterisasi Modifikasi Mikropartikel Magnetit (Fe3O4) Dalam Pemanfaatan Karat dengan Ekstrak Daun Ilalang (Imperata Cylindrica L): Synthesis and Characterization of Modified Magnetite Microparticles (Fe3O4) in Rust Utilization with Leaf Extract of Grass (Imperata cylindrica L) - Siti Zulaicha, Annisaa; Syahjoko Saputra, Iwan; Puspita Sari, Indah; Annas, Dicky (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Palangka Raya, 2020)
The synthesis of magnetite (Fe3O4) microparticles has been successfully carried out using rust and leaf extract of grass (Imperata cylindrica L). The purpose of this research is the synthesis and characterization of Fe3O4 microparticles using the Green Synthesis method. The UV-Vis results showed that the absorption peak was at a wavelength of 273 nm with an absorbance value of 0.75. FTIR analysis shows the shift of the peak at wave number 3356 cm-1 to 3290 cm-1 and the appearance of a new peak at wave number 500 cm-1 which is characteristic of the Fe-O-Fe functional group and indicates the formation of Fe3O4 microparticles. XRD results showed six specific peaks, which were crystallinity of Fe3O4 microparticles at position 2 theta 30.40 °, 35.70 °, 43.30 °, 53.80 °, 57.40 °, and 63.00 °. PSA analysis showed that the mean particle size was > 100 nm, and the PZC results showed a zeta potential of 20 mV. SEM results showed the morphology of Fe3O4 microparticles with 1000x magnification, and EDS analysis results showed Fe and O's elemental composition.